1996
DOI: 10.1177/096805199600300310
|View full text |Cite
|
Sign up to set email alerts
|

The in vivo significance of antibiotic-induced endotoxin release in experimental Gram-negative sepsis

Abstract: Considerable evidence now supports the experimental findings that penicillin-binding protein (PBP)-2 specific antimicrobial agents such as imipenem generate less endotoxin than PBP-3 specific agents such as ceftazidime during the process of bacteriolysis of Gram-negative bacteria. To determine if differences in endotoxin release have pathophysiologic significance in vivo, Sprague-Dawley rats were experimentally challenged with intraperitoneal injections of virulent, serum-resistant clinical strains of the foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 20 publications
1
17
0
Order By: Relevance
“…[22][23][24][25][26][27] The data presented here have shown that both ceftazidime and aztreonam treatment markedly enhanced LPS release from E. coli in comparison to imipenem treatment. In this respect, consistent with the observations reported here, previous reports from this laboratory and others have demonstrated that ceftazidime and aztreonam have greater ability than imipenem in vitro and ex vivo to induce LPS release, as well as production of cytokines such as TNF-a and IL-6.…”
Section: Discussionmentioning
confidence: 69%
“…[22][23][24][25][26][27] The data presented here have shown that both ceftazidime and aztreonam treatment markedly enhanced LPS release from E. coli in comparison to imipenem treatment. In this respect, consistent with the observations reported here, previous reports from this laboratory and others have demonstrated that ceftazidime and aztreonam have greater ability than imipenem in vitro and ex vivo to induce LPS release, as well as production of cytokines such as TNF-a and IL-6.…”
Section: Discussionmentioning
confidence: 69%
“…In D-galactosamine-sensitized mice infected with an LD 50 dose of P. aeruginosa, treatment with imipenem decreased mortality to 0%, whereas an equivalent dose of ceftazidime increased mortality in comparison to untreated animals (90). Similarly, in sepsis models of E. coli and P. aeruginosa infection in D-galactosamine-treated rats, imipenem therapy resulted in lower levels of circulating endotoxin and TNF and reduced mortality compared to ceftazidime treatment (127).…”
Section: Sepsismentioning
confidence: 98%
“…The potential of antibiotics to cause endotoxin release influenced the outcome of gram-negative sepsis in animal models (25,79,127). In mouse models of E. coli and P. aeruginosa peritonitis/sepsis, where bacteria, D-galactosamine (to sensitize mice for endotoxin), and antibiotics were given at the same time, 20 mg of the PBP-2 inhibitor imipenem per kg resulted in an approximately eightfold increase in the 50% lethal dose (LD 50 ) of bacteria.…”
Section: Sepsismentioning
confidence: 99%
“…PII: S 0 9 2 8 -8 2 4 4 ( 9 8 ) 0 0 0 8 4 -4 detrimental to the host with the Gram-negative bacterial infection [13,14]. Opal et al [11] showed a signi¢cant di¡erence between ceftazidime and imipenem in the plasma concentration of endotoxin released after antibiotic treatment in the Escherichia coli and Pseudomonas aeruginosa sepsis rat models. These results provided supportive evidence that differences in the plasma endotoxin concentration may re£ect the mode of antibacterial action of the antibiotics.…”
Section: Introductionmentioning
confidence: 99%
“…A number of in vivo studies have presented data indicating that antibiotic treatment can cause an increase in the plasma endotoxin concentration [3,5,8,11,13] and that released endotoxin may be 0928-8244 / 98 / $19.00 ß 1998 Federation of European Microbiological Societies. Published by Elsevier Science B.V. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%